Risk Assessment of AC/DC Hybrid Distribution Network considering New Energy and Electric Vehicle Access - Dong, Jie; Zhao, Jianjun; Liu, Ziyue; Li, Yang; Yu, Zhongshu; Liu, Jialin; Wang, Zhenhao (Frontiers in Energy Research, 2022)
In view of the operational risk issues such as safety and economy caused by the connection of new energy and multiple types of electric vehicles (EVs) to the AC-DC distribution network, an AC-DC distribution network operational risk assessment method that takes into account multiple risk factors is proposed. Firstly, a probability distribution model of scenery output and EV timing is constructed, and the starting charge state of multiple types of EVs is replaced by the number of daily driving miles subjectively set; then, based on the complex network theory, timing safety indicators such as voltage overrun risk and branch power overload operation risk are proposed, and economic risk is established according to the economic operation of the distribution grid; Furthermore, a risk assessment matrix for grid-connected EVs with different capacities is constructed, and the principal component analysis (PCA) method is used to reduce the dimension of the risk assessment matrix and calculate the objective weight coefficient; Finally, taking the improved IEEE 33 node AC/DC power distribution system as an example, and the comprehensive risk evaluation based on PCA is compared with the traditional one, the results show that when the safety and economic risk factors are considered at the same time, the operation risk in a certain range has a downward trend when the proposed method is adopted, which has a positive guiding significance for the planning of EV capacity in a certain area.